2008
DOI: 10.1007/s11606-008-0514-3
|View full text |Cite
|
Sign up to set email alerts
|

Part-Time Physicians…Prevalent, Connected, and Satisfied

Abstract: OBJECTIVE:The health care workforce is evolving and part-time practice is increasing. The objective of this work is to determine the relationship between part-time status, workplace conditions, and physician outcomes. DESIGN:Minimizing error, maximizing outcome (MEMO) study surveyed generalist physicians and their patients in the upper Midwest and New York City. MEASUREMENTS AND MAIN RESULTS:Physician survey of stress, burnout, job satisfaction, work control, intent to leave, and organizational climate. Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 18 publications
(16 reference statements)
3
57
2
1
Order By: Relevance
“…Definitions of the variables are provided in Table 1 previous literature, [17][18][19] our findings also suggest that physicians with lower clinical FTEs had higher patient satisfaction scores, after accounting for direct and indirect associations with continuity and access to care measures. Overall, this work suggests that PCPs who choose to work fewer clinical hours may have worse continuity and access outcomes, but they may provide a better patient experience.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Definitions of the variables are provided in Table 1 previous literature, [17][18][19] our findings also suggest that physicians with lower clinical FTEs had higher patient satisfaction scores, after accounting for direct and indirect associations with continuity and access to care measures. Overall, this work suggests that PCPs who choose to work fewer clinical hours may have worse continuity and access outcomes, but they may provide a better patient experience.…”
Section: Discussionsupporting
confidence: 52%
“…13 However, there are several possible reasons why physicians with fewer clinical full time equivalents (FTEs) may have higher patient satisfaction scores. Studies have shown that part-time physicians experience higher work satisfaction and less burnout than full-time physicians, 19,20 which may be attributed to an increased sense of control in setting one's schedule, 19 feeling less time pressure with patients, 21 or better work-life balance. 22,23 There is a well-established association between patient and physician satisfaction, 21 perhaps because more satisfied physicians may communicate better, 24 be more empathetic, 24 and better address their patients' concerns.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have been conflicting with regard to part-time physicians' need to make compromises with regard to their duties compared with those who work full-time. [13][14][15] Our data indicate that the opposite is more likely to be true, at least for general 7 by guest on April 29, 2019 www.aappublications.org/news Downloaded from pediatricians. It is possible that the relatively high percentage of parttime pediatricians has created more power in the marketplace or that those who work part-time have fewer demands regarding their professional and clinical duties as long as they are able to work part-time.…”
Section: Current Positions Versus Desired Professional and Clinical Rmentioning
confidence: 77%
“…20 The operational cost of replacing a primary care physician has been estimated at $250,000. 21 If retention rates are higher among part-time faculty because of higher job satisfaction, 22 or if part-time faculty fill urgent gaps in service needs, hiring part-time faculty may lead to overall cost savings in recruitment. Further, part-time clinicians, educators, and researchers may actually be more productive than their full-time counterparts because of more flexibility of time and energy.…”
Section: Costsmentioning
confidence: 99%
“…22 Job dissatisfaction and burnout can potentially translate into decrements in morale and productivity, which are hidden-but real-costs to institutions. The implications of these qualitative factors can be considerable; part-time faculty, who are less susceptible to such factors, may consequently improve patient satisfaction and productivity as well as recruitment and retention.…”
Section: Costsmentioning
confidence: 99%